DESAIN PENELITIAN SURVEI - Ladia; Mahathma Rizal Alhadad; Dina Hermina (PT. Hasba Edukasi Mandiri, 2025)
Survey research is one of the most widely used research methods across various fields to collect data from a large number of respondents. This method aims to understand the characteristics, opinions, or behaviors of a population based on a selected sample. This paper provides an in-depth discussion on survey research design, covering types of surveys, sampling techniques, data collection instruments, and data analysis methods. Additionally, it examines the advantages and limitations of the survey method, including factors that may affect the validity and reliability of research findings. By understanding the fundamental principles of survey research design, researchers can develop more systematic studies and obtain accurate and representative data to support better decision-making.